CYTOTOXIC EFFECT OF AQUADEST, ETHANOLIC, AND CHLOROFORM EXTRACTS OF Spathoglottis plicata Blume ON BREAST CANCER CELLS LINE (T47D CELLS) - Holle, Mukhlish Jamal Musa; Puspitasari, Hestri Dyah; Satryo, Andaru; Ningrum, Wahyu Dewi Astuti; Sudigyo, Digdo; Nuriliani, Ardaning (KnE Life Sciences, 2015)
Breast cancer is one of cancer with high mortality. This cancer not only attacks women, but also men. Indonesia has many plants which potential as anticancer, such as orchids. Spathoglottis plicata is one of the orchid species that abundant in Indonesia and has a lot of antioxidant compounds which is guessed have anticancer properties. The objectives of this study were to study the cytotoxic activity and IC50 value of aquadest, ethanolic, and chloroform extracts of S. plicata’s pseudobulbs, leaves, and whole plants on T47D cells (breast cancer cells line) as well as cytotoxic activity of the specific fraction of the most toxic crude extract. S. plicata used in this study was obtained from Bungarinte nursery. Extractions were done by maceration method using aquadest, ethanol, and chloroform as the solvent. Cytotoxic test on T47D cells were done by MTT assay. The cytotoxic data were analyzed using one-way ANOVA followed by Tukey’s HSD test. The IC50 of each extracts were calculate by probit analysis. The lowest IC50 value among all extracts was fractionated and isolated by preparative TLC. The cytotoxic activity and IC50 of this fractions were analyzed. The results showed that only 2 from 9 crude extracts that able to calculate its IC50 because those two extracts have concentration dependent pattern of inhibition concentration. Chloroform extract have the lowest IC50 value (369,837 μg/mL). Then, this extract fractionated by eluen n-hexane : ethyl acetate 4:1. Four fractions were collected. The lowest IC50 value is fraction IV (144,41 μg/mL). Based on the results it could be concluded that S. plicata leaves have moderate potency to develop as anticancet agents, especially on breast cancer. Keywords: S. plicata, T47D cells, cytotoxic, MTT assay, preparative TLC.